Comparative Elucidation of Age, Diameter, and “Pockmarks” in Roots of Paeonia lactiflora Pall. (Shaoyao) by Qualitative and Quantitative Methods - Zheng, Xiaowen; Yin, Minzhen; Chu, Shanshan; Yang, Mei; Yang, Zhengyang; Zhu, Yuejian; Huang, Luqi; Peng, Huasheng (Frontiers in Plant Science, 2022)
Paeonia lactiflora Pall. is a world-famous ornamental plant, whose roots have been used as an important traditional Chinese medicine, Shaoyao, to treat diseases for more than 1,000 years. Because of the excellent curative effect of Shaoyao, its quality has attracted wide attention, however, there is a lack of comprehensive research on the different influencing factors of quality of Shaoyao. In this study, ultra-performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF-MS) and high-performance liquid chromatography with diode-array detection (HPLC-DAD) were utilized to systematically analyze the Shaoyao of different ages, diameters and roots with “pockmarks”. 60 metabolites were detected and identified from Shaoyao using the UPLC-Q/TOF-MS, of which 20 potential quality markers of dissected roots with and without “pockmarks” were selected for the first time using the orthogonal partial least squares discriminant analysis (OPLS-DA) and the variable importance for projection (VIP) plot. Then, a selective and accurate HPLC-DAD quantitative assay has been developed for the simultaneous determination of 11 bioactive components in Shaoyao. The results showed that the total content of five monoterpene glycosides including oxypaeoniflorin, albiflorin, paeoniflorin, lactiflorin and benzoylpaeoniflorin and six phenols including gallic acid, catechin, methyl gallate, ethyl gallate, apiopaeonoside and benzoic acid in the 3-year-old Shaoyao was higher than that of 4-year-old and 5-year-old Shaoyao. In Shaoyao of the same age, the total content of five monoterpene glycosides and six phenols decreased with an increase in diameter. In addition, regardless of whether it is a whole or a divided root, the contents of five monoterpene glycosides and six phenols in Shaoyao with “pockmarks” were higher than those of Shaoyao without “pockmarks”. In summary, this work has explored several factors that might affect the quality of Shaoyao, and provide a guide for more comprehensive quality evaluation in its further production, processing, and rational utilization.